Prognostic impact of HER2-low expression in hormone receptor positive early breast cancer. (December 2021) - Mutai, Raz; Barkan, Tamar; Moore, Assaf; Sarfaty, Michal; Shochat, Tzippy; Yerushalmi, Rinat; Stemmer, Salomon M.; Goldvaser, Hadar
Abstract: Background: Recent data suggest that human epidermal growth factor receptor 2 (HER2)-low breast cancer may represent a distinct entity. We aimed to compare disease characteristics and outcomes between HER2-low and HER2-0 in estrogen receptor (ER) positive, early-stage breast cancer. Methods: A single center retrospective study comprising all women with ER positive, HER2 negative early breast cancer, for whom an Oncotype DX test was performed between 2005 and 2012. Women were grouped to HER2-low (immunohistochemistry +1 or +2 and in situ hybridization not amplified) or HER2-0. Clinico-pathological features and Oncotype recurrence score (RS) were collected. Data on overall-survival (OS), disease-free survival (DFS) and distant disease-free survival (DDFS) were evaluated according to HER2 expression status. Results: 608 women were included, of which 304 women had HER2-0 and 304 had HER2-low disease. Lobular subtype was significantly more common in HER-0 compared to HER2-low disease (17% vs. 8%, p = 0.005). The prevalence of other clinic-pathological characteristics and long-term prognosis were comparable between both groups. For women with high genomic risk (RS > 25), HER2-low expression was associated with significantly favorable OS (HR = 0.31, 95% CI 0.11–0.78, p  =  0.01), DFS (HR = 0.40, 95% CI 0.20–0.82, p = 0.01) and DDFS (HR = 0.26, 95% CI 0.11–0.63, P = 0.002) compared to women with HER2-0. For women with low genomic risk (RS ≤ 25), long-term prognosis was unrelated to HER2 expression. Conclusion: The prognostic impact of HER2-low expression in early-stage luminal disease varies across the genomic risk, with significant favorable outcomes of HER2-low expression compared to HER2-0 in women with high genomic risk. Highlights: The dichotomous categorization of HER2-positive and HER2-negative breast cancer has been challenged. The prognostic impact of HER2-low expression differs between Oncotype-DX risk groups. High risk (RS > 25) HER2-low disease is associated with significantly favorable outcomes compared to HER2-0. Outcomes for low genomic risk (RS < 25) HER2-low vs. HER2-0 were similar. These novel findings may point on a new prognostic feature of early-stage, high genomic risk luminal disease.